PENGARUH MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS IV SD BAWAKARAENG 1 - Ninis Puspita; Suci Ramadani; Faika Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low science learning outcomes of fourth-grade students at SD Bawakaraeng 1, particularly on plant parts material which is often presented textually without engaging physical media. This study aims to analyze the effect of using physical learning media on student learning outcomes in that topic. The method used is quantitative with a quasi-experimental One Group Pretest-Posttest Design involving 23 fourth-grade students. Data were collected through test instruments (pretest and posttest) and analyzed using the paired sample t-test. The results showed an increase in the mean score from 51.52 to 70.43. A significance value of p<0.001 (p<0.05) indicates that the use of physical media has a significant impact on student achievement. This study concludes that integrating learning media in the form of teaching aids is effective in transforming abstract biological concepts into more concrete ones for elementary students. It is recommended that teachers utilize local teaching aids to support more interactive and contextual science learning.